A Study on the Ability in Using Preposition of Place in Speaking Performance - Manu, Detilda; Kamlasi, Imanuel (Journal of Teaching of English, 2022)
The objectives of the research were to find out students’ level ability in using prepositions of place in speaking performance and to find out the difficulties prepositions of place for students in speaking performance. This study used descriptive qualitative method to analyze and describe data. The instrument was oral test. The sample of the study was purposive sampling of second semester students of English Study Program of Timor University. The total students were 25 participants. The result showed that from the twenty-five students who did the speaking test, 23 students passed the test, 2 did not pass the test. The higher score was 100, lowest score was 62. Students’ average score was 83. The students’ level ability is good. It means they were able in using prepositions of place in speaking performance. This due to the score gained. The score reveals that about, of, above, among and for were the difficulties prepositions of place.